Short‐term experiences of a liver transplant centre before and after the COVID‐19 pandemic. Issue 10 (5th August 2021) - Altunisik Toplu, Sibel; Bayindir, Yasar; Yilmaz, Sezai; Yalçınsoy, Murat; Otlu, Baris; Kose, Adem; Sahin, Tevfik Tolga; Akbulut, Sami; Isik, Burak; Başkiran, Adil; Koc, Cemalettin
Abstract: Background/Aim: With the COVID‐19 pandemic, managing the process of solid organ transplantation has become a significant matter for transplant centres. In this study, we report our experiences on evaluating the effects of COVID‐19 in patients with recent liver transplants. Materials and Methods: We evaluated patients who received liver transplants during three close consecutive periods of time. For transplants conducted between October 1 and December 31, 2019, January 1 and March 10, 2020 and March 11 and June 22, 2020, the lung tomographies of patients were inspected for radiological signs of viral pneumonia. For patients after March 11, 2020, the hospital's electronic database system was scanned for preoperative and postoperative SARS‐CoV‐2 testing from Real‐time Polymerase Chain Reaction (RT‐PCR) of the respiratory tract samples. Results: A total of 149 patients over the age of 18 who received liver transplants at our centre between October 1, 2019 and June 22, 2020 were evaluated. During this time span, our centre conducted liver transplants on patients from 34 different provinces and also abroad. Within this time period, a total of nine patients had respiratory samples with a positive SARS‐CoV‐2 RT‐PCR test. PCR of respiratory tract samples was performed in 21 (14%) patients to identify the other potential infective agents in the respiratory tracts; Rhinovirus and Influenza A were detected in two and respiratory syncytial virus (RSV) was detected in one patient. During the transplant periods, 99 (67.1%) patients were evaluated with computed tomography (CT). The CT findings of 18 (12%) patients were consistent with viral pneumonia. There was a statistically significant difference between the groups only in terms of air bronchogram findings ( P  = .012). Conclusion: The clinical status of our short‐term liver transplant patients was far better than we originally anticipated, but it remains obvious that the necessary precautions should continue to be taken.